Analgesic efficacy of perioperative use of vedaprofen, tramadol or their combination in cats undergoing ovariohysterectomy - Brondani, Juliana Tabarelli [UNESP]; Loureiro Luna, Stelio Pacca [UNESP]; Beier, Suzane Lilian [UNESP]; Minto, Bruno Wanatabe [UNESP]; Padovani, Carlos Roberto [UNESP] (Elsevier B.V., 2009)
The analgesic efficacy of tramadol and/or vedaprofen was evaluated in cats submitted for elective ovariohysterectomy, using a randomised double blind placebo controlled design. Forty adult female cats (3.0 +/- 0.32 kg; 1.8 +/- 0.7 years) were distributed into four groups. Vedaprofen PO (0.5 mg/kg), tramadol SC (2 mg/kg), both, or placebo was administered 1 h before surgery and every 24 and 8 h, respectively, for 72 h after surgery. Pain score evaluated by interactive visual analogue and composite pain score and hyperalgesia by the von Frey filament test were recorded at 1, 2, 4, 6, 8, 12, 24, 28, 32, 48, 52, 56, 72, 96 h and on the 7th day after surgery. Animals treated with combined vedaprofen and tramadol treatment did not need rescue analgesia, did not develop hyperalgesia, and their serum cortisol concentrations and pain scores were lower than placebo until 24 and 72 h after surgery, respectively. Combined vedaprofen and tramadol treatment provided more effective postoperative analgesia and prevented hyperalgesia than when used on their own. Multimodal technique is a superior method of treating pain after feline ovariohysterectomy. This work also provides evidence for the benefits of analgesia for up to 3 days following ovariohysterectomy. (C) 2008 ESFM and AAFP. Published by Elsevier Ltd. All rights reserved.